Brassinolide promotes interaction between chloroplasts and mitochondria during the optimization of photosynthesis by the mitochondrial electron transport chain in mesophyll cell protoplasts of Arabidopsis thaliana - Mahati, Kandarpa; Padmasree, Kollipara (Frontiers in Plant Science, 2023)
The current experimental data unveils the role of brassinolide (BL), a phytohormone of class brassinosteroids (BRs), in augmenting the cross-talk between the mitochondrial electron transport chain (mETC) and chloroplasts to strengthen the efficiency of the Calvin-Benson cycle (CBC) for higher assimilation of carbon dioxide in the mesophyll cell protoplasts (MCP) of Arabidopsis thaliana. The outcome of total respiration (TR) and photosynthetic carbon assimilation (PCA) was monitored as O2 uptake under dark and NaHCO3-dependent O2 evolution under light, respectively, after pre-incubation of MCP at a broad spectrum of BL concentration from 0.05 pM to 5 pM at 25 °C and optimum light intensity of 1000 μmol m-2 s-1. The addition of optimal concentration (0.5 pM) of BL to MCP stimulated the (i) TR, (ii) PCA, and (iii) para-benzoquinone-dependent O2 evolution (PSII activity). Further, in response to BL, the enzyme activity or transcript levels of redox-regulated CBC enzymes and glucose-6-phosphate raised considerably. Also, the addition of BL to MCP remarkably accelerated the capacity of the cytochrome oxidase (COX) and alternative oxidase (AOX) pathways concurrently with an increase in total cellular pyruvate and reactive oxygen species (ROS) levels. Besides, malate valve components (Malate, Chl-MDH, M-MDH) increased in response to BL. At the same time, the cellular redox ratios of pyridine nucleotides (NADPH and NADH) were kept low in the presence of BL. However, BL could not keep up the CBC activity of photosynthesis along with its associated light-activated enzymes/transcripts when mETC through COX or AOX pathway is restricted by antimycin A (AA) or salicylhydroxamic acid (SHAM), respectively. In contrast, adding BL to MCP under restricted mETC showed aggravation in total cellular ROS, pyruvate, malate, and redox ratio of pyridine nucleotides with a concomitant increase in transcripts associated with malate valve and antioxidant systems. These results suggest that BL enhances the PCA by coordinating in cross-talk of chloroplasts and mitochondria to regulate the cellular redox ratio or ROS through the involvement of COX and AOX pathways along with the malate valve and antioxidant systems.